Arte e vida do Vale do Jequitinhonha: um museu virtual na escola - Norali Barbosa Esteves de Oliveira (2023)
In this study, the importance of bringing Art, which is produced in the Vale do Jequitinhonha, closer to the school context is highlighted. Seeking with the students evidence that they can reveal, point out how they perceive themselves (or not) in their historicity, in the art and in the artists of the region. Based on field research with students in the 9th grade of elementary school at the state school Frei Rogato, located in Araçuaí - Vale do Jequitinhonha, Minas Gerais, we sought to promote their approximation to the art of the place where they live, bringing them as protagonists of its history and of the art produced in the Vale; whose study took place during the COVID-19 pandemic. As a consequence, the pedagogical proposal of creating a virtual art museum developed by the students arises. To give visibility to the path taken, contributions from art and education were used, such as Delory-Momberger (2006), Freire (1996), Pimentel (2011), Richter (2008), Saviani (2008) and other authors relevant to the theme.